PNPLA3 rs738409 underlies treatment response in nonalcoholic fatty liver disease - Wang, Jin-Zhi (World J Clin Cases, 2018)
Non-alcoholic fatty liver disease (NAFLD) has now become the leading cause of chronic liver disease with its growing incidence worldwide. Patatin-like phospholipase domain-containing protein 3 (PNPLA3) rs738409 C > G reflects one of the critical genetic factors that confers high-risk to NAFLD. However, the role of PNPLA3 polymorphism in NAFLD treatment remains uncertain. Here, the present review reveals that NAFLD patients with G-allele at PNPLA3 rs738409 (PNPLA3 148M variant) are sensitive to therapies of lifestyle modification, dipeptidyl peptidase-4 inhibitors, and bariatric surgery. They exhibit much significant reduction of liver fat content, in concurrence with weigh loss and abolished insulin resistance, as compared to those of C-allele carriers. In contrast, patients bearing PNPLA3 rs738409 C-allele (PNPLA3 148I variant), instead of G-allele, demonstrate greater beneficial effects by omega-3 poly-unsaturated fatty acids and statin intervention. Improved adipose tissue-liver interaction and decrease in intrahepatic triglyceride efflux may contribute to the PNPLA3 rs738409 related diversities in therapeutic efficacy. Therefore, PNPLA3 rs738409 underlies the response to a variety of treatments, which warrants a personalized, precise medicine in NAFLD on the basis of genotype stratification.